Karakteristik Struktur Teks Cerpen Siswa Kelas XI SMA Negeri 4 Pariaman - Puja Andrilla (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
(Objective) This study aims to describe the characteristics of the short story text structure of the students of Class XI SMAN 4 Pariaman,. Analysis using structural analysis. (Method) The method used in this research is descriptive method. The data collection technique used is the fishing rod technique. (Findings) The results of this study indicate that the short stories text structure of class XI students of SMAN 4 Pariaman for the academic year 2021/2022 have differences and have their respective characteristics between the short stories of students in class XI of SMAN 4 Pariaman for the academic year 2021/2022 and the short stories of Si Padang.